2009
DOI: 10.1128/ec.00190-09
|View full text |Cite
|
Sign up to set email alerts
|

Mss11, a Transcriptional Activator, Is Required for Hyphal Development in Candida albicans

Abstract: Candida albicans undergoes a morphological transition from yeast to hyphae in response to a variety of stimuli and growth conditions. We previously isolated a LisH domain containing transcription factor Flo8, which is essential for hyphal development in C. albicans. To search the putative binding partner of Flo8 in C. albicans, we identified C. albicans Mss11, a functional homolog of Saccharomyces cerevisiae Mss11, which also contains a LisH motif at its N terminus. C. albicans Mss11 can interact with Flo8 via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
3
25
1
Order By: Relevance
“…From previously published genetic epistasis studies, Mss11p may be acted upon by many filamentous growth factors, including the transcriptional regulators PHD1, NRG1/2, and FLO8 itself (68); thus, in S. cerevisiae, Mss11p is thought to act downstream of Flo8p. In C. albicans, however, Flo8p and Mss11p physically interact with each other and may cooperatively bind target gene promoters (75). Similar results have been found in Saccharomyces diastaticus, where Mss11p and Flo8p bind cooperatively to the sequence TTTGCnGCAAA (n ϭ 97) in the STA1 promoter (76).…”
Section: Pun1 Is Essential For Filamentous Growth and Is An Importantsupporting
confidence: 66%
“…From previously published genetic epistasis studies, Mss11p may be acted upon by many filamentous growth factors, including the transcriptional regulators PHD1, NRG1/2, and FLO8 itself (68); thus, in S. cerevisiae, Mss11p is thought to act downstream of Flo8p. In C. albicans, however, Flo8p and Mss11p physically interact with each other and may cooperatively bind target gene promoters (75). Similar results have been found in Saccharomyces diastaticus, where Mss11p and Flo8p bind cooperatively to the sequence TTTGCnGCAAA (n ϭ 97) in the STA1 promoter (76).…”
Section: Pun1 Is Essential For Filamentous Growth and Is An Importantsupporting
confidence: 66%
“…Firstly, Sfl2 was named by Spiering et al (2009) according to its sequence similarity to Sfl1; we present the evidence for the functional correlation between Sfl2 and Sfl1 by a complementation test in S. cerevisiae (Fig. This expression pattern implies a positive role of Sfl2 in morphogenesis, considering that body temperature (37 1C) serves as a hyphal inducer and that several positive regulators of filamentation, such as TEC1, UME6, and MSS11, have been shown to be induced by morphogenetic stimuli (Schweizer et al, 2000;Su et al, 2009;Zeidler et al, 2009). Secondly, Spiering et al (2009) suggested that SFL2 transcription is upregulated by the environmental culture conditions in the RHE infection model; we show here that high temperature (37 1C) has a major impact on induction of SFL2 at both transcriptional and translational levels.…”
Section: Discussionmentioning
confidence: 93%
“…Flo8 interacts with Efg1 in yeast and hyphal cells, and Flo8 regulates a subset of genes controlled by Efg1 (92). Recently, the transcriptional activator Mss11 was shown to interact with Flo8 and influence C. albicans morphogenesis (568). The overexpression of MSS11 enhances filamentation, while the homozygous deletion of MSS11 blocks filamentation under many conditions (568).…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%
“…Recently, the transcriptional activator Mss11 was shown to interact with Flo8 and influence C. albicans morphogenesis (568). The overexpression of MSS11 enhances filamentation, while the homozygous deletion of MSS11 blocks filamentation under many conditions (568). Another transcription factor thought to act downstream of PKA is Sfl1.…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%